MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM SIRKULASI KELAS XI MELALUI PENGEMBANGAN MODUL PEMBELAJARAN BERORIENTASI MODEL GUIDED INQUIRY - Wan Syafi'i; Rini Farmita Sari; Arnentis " (Biogenesis, 2017)
ABSTRACT  The purpose of this study was to develop a learning module oriented guided inquiry model of the material circulation system of class XI in improving students' critical thinking skills. Research conducted at the Laboratory of Biology Education Studies Program Faculty of Teaching and Education University of Riau and SMAN 1 Pekanbaru in February 2015 - May 2016. The research is a research development by using ADDIE model of integration to the stage of development. Instruments of data collection in this study is the assessment sheet / validation module, student questionnaire responses and critical thinking skills assessment sheet. Once the module is developed, validated by 4 validator then the tests I at 12 4th semester students of biology education FKIP UR and II trials in 20 students in Class XI SMAN 1 Pekanbaru. The tests for aspects of the content presented, language, presentation and kegrafisan module obtained an average score 4.20 (valid). Aspects of the content presented is obtained an average score 4.28 (very valid), aspects of language obtained a score 4.07 (valid), then to obtain a grain aspect score 4.16 (valid) and aspects of kegrafisan obtain an average score 4.30 (very valid). In the student questionnaire responses in the experiment I belong to the category module SB (Very Good), while the second test the response of 20 students of the modules developed is 84% in one study and 82% in the second study with either category. As for the average results of analysis of students' answers on the learning modules acquire 82% considered good value. Based on the results of data analysis can be seen that the module-oriented model of guided inquiry learning to enhance students' critical thinking skills in class XI material circulation system that has been developed can already be used with a valid category.  Key words: Development, Module, Guided Inquiry, Critical thinking, System CirculationABSTRACT  The purpose of this study was to develop a learning module oriented guided inquiry model of the material circulation system of class XI in improving students' critical thinking skills. Research conducted at the Laboratory of Biology Education Studies Program Faculty of Teaching and Education University of Riau and SMAN 1 Pekanbaru in February 2015 - May 2016. The research is a research development by using ADDIE model of integration to the stage of development. Instruments of data collection in this study is the assessment sheet / validation module, student questionnaire responses and critical thinking skills assessment sheet. Once the module is developed, validated by 4 validator then the tests I at 12 4th semester students of biology education FKIP UR and II trials in 20 students in Class XI SMAN 1 Pekanbaru. The tests for aspects of the content presented, language, presentation and kegrafisan module obtained an average score 4.20 (valid). Aspects of the content presented is obtained an average score 4.28 (very valid), aspects of language obtained a score 4.07 (valid), then to obtain a grain aspect score 4.16 (valid) and aspects of kegrafisan obtain an average score 4.30 (very valid). In the student questionnaire responses in the experiment I belong to the category module SB (Very Good), while the second test the response of 20 students of the modules developed is 84% in one study and 82% in the second study with either category. As for the average results of analysis of students' answers on the learning modules acquire 82% considered good value. Based on the results of data analysis can be seen that the module-oriented model of guided inquiry learning to enhance students' critical thinking skills in class XI material circulation system that has been developed can already be used with a valid category.  Key words: Development, Module, Guided Inquiry, Critical thinking, System Circulation